Non-thermal resistive switching in Mott insulator nanowires - Yoav Kalcheim (Nature Portfolio, 2020)
Despite intensive research on the electrically driven insulator-to-metal transition, this phenomenon is not well understood. Using quasi 1D nanowires of two Mott insulators, the authors reveal the central role of defects in enabling a non-thermal doping driven insulator-to metal transition.